An Ayurvedic Management Of Pandu Roga (Anaemia)- A Review - verma, Preeti; Mishra, Pramod Kumar; Sharma, Barhmanand; Gautam, Vinod Kumar (International Research Journal of Ayurveda & Yoga, 2021)
Anaemia is defined as the qualitative or quantitative diminution of RBC and /or hemoglobin concentration to carry adequate oxygen to the body’s tissue in relation to standard age and sex, and is clinically manifested by pallor. The clinical condition of anaemia especially iron deficiency anaemia can be correlated with Pandu Roga in Ayurveda. It is mentioned in all ayurvedic texts such as CharakSamhita, Susruta Samhita, Astanga Hrudaya etc. Rasavaha and Raktavaha Srotas are chiefly involved in pathogenesis of Pandu roga. The Anna-rasa nourishes all Dhatus, while the Kitta-bhag is excreted out. The Anna-rasa is produced by the action of Jatharagni on Ahara. When there is hypo functioning of Jatharagni, which produce improper Anna-rasa and its leads to the formation of abnormal Rasa Dathu and will consequently produce abnormal and deficient Rakta Dhatu. Thus the deficient of Rakta Dhatu resulting symptoms are appear like Pandu varana, Rakta Alpata, Durbalta, etc. In this series, ultimately there is diminution of the vital essence i.e. Ojus. As a result of above, the individual becomes Nihsara (insipid) and Pandu is produced. General principles of the management of any disorder in Ayurveda is divided in three parts, like Nidana Parivarjan, Sansodhan Chikitsa, Sansaman Chikitsa. In this review article we made an effort to explain the etiology, pathogenesis, signs & symptoms, investigations and Ayurvedic management of Pandu Roga (anaemia).